2021
DOI: 10.1136/bmjgh-2021-006204
|View full text |Cite
|
Sign up to set email alerts
|

Disruption in essential health services in Mexico during COVID-19: an interrupted time series analysis of health information system data

Abstract: IntroductionThe COVID-19 pandemic has disrupted health systems around the world. The objectives of this study are to estimate the overall effect of the pandemic on essential health service use and outcomes in Mexico, describe observed and predicted trends in services over 24 months, and to estimate the number of visits lost through December 2020.MethodsWe used health information system data for January 2019 to December 2020 from the Mexican Institute of Social Security (IMSS), which provides health services fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
116
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(122 citation statements)
references
References 35 publications
6
116
0
Order By: Relevance
“…In South Africa, a retrospective study that included adults and children showed a decrease only in child health visits, and there was no change in primary care visits for adults ( 43 ). In Mexico, on the other hand, a decrease was found in sick child visits and contraceptive services by ~50%, the number of diabetes, hypertension, and antenatal care consultations by ~33.3%, and the number of deliveries attended at The Mexican Institute of Social Security by 10% ( 44 ). Authors from Romania found that the rate of continuous hospitalization decreased due to cardiovascular diseases by 46.99%, digestive diseases by 47.37%, respiratory diseases by 37.28%, and the rate of admission due to mental and behavioral disorders decreased by 55% for continuous hospitalization and ~67% for day hospitalization ( 45 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In South Africa, a retrospective study that included adults and children showed a decrease only in child health visits, and there was no change in primary care visits for adults ( 43 ). In Mexico, on the other hand, a decrease was found in sick child visits and contraceptive services by ~50%, the number of diabetes, hypertension, and antenatal care consultations by ~33.3%, and the number of deliveries attended at The Mexican Institute of Social Security by 10% ( 44 ). Authors from Romania found that the rate of continuous hospitalization decreased due to cardiovascular diseases by 46.99%, digestive diseases by 47.37%, respiratory diseases by 37.28%, and the rate of admission due to mental and behavioral disorders decreased by 55% for continuous hospitalization and ~67% for day hospitalization ( 45 ).…”
Section: Resultsmentioning
confidence: 99%
“…Similar outcomes were observed in Nepal, where the supply of medicines was the worst affected area of healthcare delivery next to immunization and maternity services ( 50 ). Furthermore, in Kenya, HPV vaccination was disrupted, and BCG, pentavalent, rotavirus, and pneumococcal vaccination were declined in Mexico ( 37 , 44 ). Significant declines in receipt of IFA supplements for pregnant women were observed in Bangladesh ( 42 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The vertical grey dashed line is the start of the IMSS national strategy for health services recovery (1 April 2021). The definitions of the indicators of services use presented in this figure can be found in the previously published article by Doubova et al 9 . For instance, the indicator on children vaccination included information on Bacillus Calmette-Guérin vaccine; the rotavirus vaccine; the pentavalent vaccine against diphtheria, tetanus, pertussis, polio and Haemophilus influenzae type B; the pneumococcal vaccine; and the measles, mumps and rubella vaccine applied in children 0–9 years.…”
Section: Imss National Strategy For Health Services Recoverymentioning
confidence: 99%
“…Diabetes prevalence, as well as diabetes-related complications and mortality, are tightly associated with socio-demographic inequalities 2,3 . These inequalities were unmasked by the COVID-19 pandemic, in part due to a fragmented care infrastructure that preceded COVID-19 and interruptions in in-person care, which disproportionately impacted socioeconomically vulnerable populations 6,7 . As such, while the intersection of diabetes and COVID-19 and their compounded severity was an important contributor to all-cause excess mortality in Mexico in 2020 [8][9][10] , the pandemic had ripple effects that also impacted care continuity for people with diabetes independent of COVID-19 itself.…”
Section: Introductionmentioning
confidence: 99%